(untitled) (Proceedings of Voronezh State University. Series: Geology, 2019)
the airborne magnetic method has more applications in prospecting and exploration for mineral deposits comparing to other airborne geophysical methods, and mainly leads to better results. The airborne magnetic data was acquired along primary lines spaced at 1000 m and along control lines spaced at 10000 m, (normal to the primary lines. Nominal flying elevation was about 100 m above ground surface (terrain clearance). An overview of the calibration and processing steps of the airborne magnetic data is presented and applied on the data. The Reduction to pole (RTP) map is created from total magnetic intensity map. Results showed that there are two major zones within the study area. The first zone is located in the Eastern side of the area extended to southwestern part of the area which is characterized by high magnetic amplitude. The second zone encountered in the western and southeastern side of the area and characterized by low magnetic amplitude.